CN118166345A - An oxalate system composite conversion film for steel substrate and its application method - Google Patents

An oxalate system composite conversion film for steel substrate and its application method Download PDF

Info

Publication number
CN118166345A
CN118166345A CN202410304222.6A CN202410304222A CN118166345A CN 118166345 A CN118166345 A CN 118166345A CN 202410304222 A CN202410304222 A CN 202410304222A CN 118166345 A CN118166345 A CN 118166345A
Authority
CN
China
Prior art keywords
system composite
composite conversion
oxalate system
steel substrate
concentration
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
CN202410304222.6A
Other languages
Chinese (zh)
Inventor
冯立明
张恒
高晓雨
冯以盛
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Shandong Jianzhu University
Original Assignee
Shandong Jianzhu University
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Shandong Jianzhu University filed Critical Shandong Jianzhu University
Priority to CN202410304222.6A priority Critical patent/CN118166345A/en
Publication of CN118166345A publication Critical patent/CN118166345A/en
Pending legal-status Critical Current

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C23—COATING METALLIC MATERIAL; COATING MATERIAL WITH METALLIC MATERIAL; CHEMICAL SURFACE TREATMENT; DIFFUSION TREATMENT OF METALLIC MATERIAL; COATING BY VACUUM EVAPORATION, BY SPUTTERING, BY ION IMPLANTATION OR BY CHEMICAL VAPOUR DEPOSITION, IN GENERAL; INHIBITING CORROSION OF METALLIC MATERIAL OR INCRUSTATION IN GENERAL
    • C23C—COATING METALLIC MATERIAL; COATING MATERIAL WITH METALLIC MATERIAL; SURFACE TREATMENT OF METALLIC MATERIAL BY DIFFUSION INTO THE SURFACE, BY CHEMICAL CONVERSION OR SUBSTITUTION; COATING BY VACUUM EVAPORATION, BY SPUTTERING, BY ION IMPLANTATION OR BY CHEMICAL VAPOUR DEPOSITION, IN GENERAL
    • C23C22/00—Chemical surface treatment of metallic material by reaction of the surface with a reactive liquid, leaving reaction products of surface material in the coating, e.g. conversion coatings, passivation of metals
    • C23C22/05—Chemical surface treatment of metallic material by reaction of the surface with a reactive liquid, leaving reaction products of surface material in the coating, e.g. conversion coatings, passivation of metals using aqueous solutions
    • C23C22/06—Chemical surface treatment of metallic material by reaction of the surface with a reactive liquid, leaving reaction products of surface material in the coating, e.g. conversion coatings, passivation of metals using aqueous solutions using aqueous acidic solutions with pH less than 6
    • C23C22/46—Chemical surface treatment of metallic material by reaction of the surface with a reactive liquid, leaving reaction products of surface material in the coating, e.g. conversion coatings, passivation of metals using aqueous solutions using aqueous acidic solutions with pH less than 6 containing oxalates
    • C—CHEMISTRY; METALLURGY
    • C23—COATING METALLIC MATERIAL; COATING MATERIAL WITH METALLIC MATERIAL; CHEMICAL SURFACE TREATMENT; DIFFUSION TREATMENT OF METALLIC MATERIAL; COATING BY VACUUM EVAPORATION, BY SPUTTERING, BY ION IMPLANTATION OR BY CHEMICAL VAPOUR DEPOSITION, IN GENERAL; INHIBITING CORROSION OF METALLIC MATERIAL OR INCRUSTATION IN GENERAL
    • C23C—COATING METALLIC MATERIAL; COATING MATERIAL WITH METALLIC MATERIAL; SURFACE TREATMENT OF METALLIC MATERIAL BY DIFFUSION INTO THE SURFACE, BY CHEMICAL CONVERSION OR SUBSTITUTION; COATING BY VACUUM EVAPORATION, BY SPUTTERING, BY ION IMPLANTATION OR BY CHEMICAL VAPOUR DEPOSITION, IN GENERAL
    • C23C22/00—Chemical surface treatment of metallic material by reaction of the surface with a reactive liquid, leaving reaction products of surface material in the coating, e.g. conversion coatings, passivation of metals
    • C23C22/78—Pretreatment of the material to be coated

Landscapes

  • Chemical & Material Sciences (AREA)
  • General Chemical & Material Sciences (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Engineering & Computer Science (AREA)
  • Materials Engineering (AREA)
  • Mechanical Engineering (AREA)
  • Metallurgy (AREA)
  • Organic Chemistry (AREA)
  • Chemical Treatment Of Metals (AREA)

Abstract

本发明提供了一种用于钢铁基体的草酸盐体系复合转化膜及其应用方法,属于化学转化膜技术领域。该转化膜的制备原料由草酸、柠檬酸钠、硝酸铈、醋酸锆和助剂组成。其中,草酸的浓度为15‑35g/L,柠檬酸钠的浓度为0.04‑2.0g/L,硝酸铈的浓度为0.02‑1.0g/L,醋酸锆的浓度为0.2‑2.0g/L,助剂的浓度为0.01‑0.1mg/L。助剂可由苯并咪唑、苯并五氮唑、聚乙二醇中的一种或几种组合而成。该复合转化膜具有良好的防锈效果,可以替代传统的磷化转化膜,实现钢铁基体的绿色防锈。

The invention provides an oxalate system composite conversion film for a steel substrate and an application method thereof, belonging to the technical field of chemical conversion films. The raw materials for preparing the conversion film are composed of oxalic acid, sodium citrate, cerium nitrate, zirconium acetate and an auxiliary agent. Among them, the concentration of oxalic acid is 15-35g/L, the concentration of sodium citrate is 0.04-2.0g/L, the concentration of cerium nitrate is 0.02-1.0g/L, the concentration of zirconium acetate is 0.2-2.0g/L, and the concentration of the auxiliary agent is 0.01-0.1mg/L. The auxiliary agent can be composed of one or more combinations of benzimidazole, benzopentazole, and polyethylene glycol. The composite conversion film has a good anti-rust effect, can replace the traditional phosphating conversion film, and realize the green anti-rust of the steel substrate.

Description

Composite conversion film of oxalate system for steel matrix and application method thereof
Technical Field
The invention belongs to the technical field of chemical conversion films, and particularly relates to an oxalate system composite conversion film for a steel matrix and an application method thereof.
Background
Phosphating of steel matrix is a widely adopted conversion film technology, is used for rust prevention, lubrication and priming before coating, has good effect and stable performance, but is greatly limited in use due to pollution of heavy metals and high phosphorus in working solution. In recent years, surface treatment technologies such as silanization, pottery and the like appear, and the coating has remarkable environmental protection advantages, but the coating is thin and low in corrosion resistance, and when the coating is used on a steel substrate, the substrate is easy to rust, so that the salt spray resistance of the whole coating system is reduced, and the coating is difficult to popularize and apply on a large scale. At present, no industrial application technology capable of really replacing phosphating on a steel matrix exists.
Oxalic acid is nontoxic and harmless, wastewater is easy to treat by adopting a precipitation method or a biochemical method, and the wastewater has remarkable environmental protection advantages, but the oxalate conversion film is thin in film layer, large in porosity and high in solubility, and corrosion resistance and mechanical properties cannot meet the requirements of rust prevention of steel and priming before coating. Therefore, how to improve the performance of oxalate conversion coating to meet the rust prevention requirement of steel is a problem that needs to be solved at present.
Disclosure of Invention
The invention aims to provide an oxalate system composite conversion film for a steel matrix and an application method thereof, so that the oxalate system composite conversion film can replace a phosphating composite conversion film preparation technology and is used for rust prevention of the steel matrix and priming before coating.
In order to achieve the above purpose, the present invention provides the following technical solutions:
the invention provides an oxalate system composite conversion film for a steel matrix, which is prepared from the following raw materials: oxalic acid, sodium citrate, cerium nitrate, zirconium acetate and an auxiliary agent.
Preferably, in the preparation raw materials of the oxalate system composite conversion film, the concentration of oxalic acid is 15-35g/L, the concentration of sodium citrate is 0.04-2.0g/L, the concentration of cerium nitrate is 0.02-1.0g/L, the concentration of zirconium acetate is 0.2-2.0g/L, and the concentration of the auxiliary agent is 0.01-0.1mg/L.
Preferably, the mass ratio of the cerium nitrate to the sodium citrate is 1:2;
The concentration of the cerium nitrate is 0.06g/L, and the concentration of the zirconium acetate is 1.0g/L;
preferably, the auxiliary agent is an aqueous solution formed by one or more of benzimidazole, benzopentazole and polyethylene glycol.
Preferably, the concentration of the benzimidazole is 0-0.05g/L, the concentration of the benzoxazoles is 0-0.05g/L, and the concentration of the polyethylene glycol is 0-0.10g/L.
Preferably, the auxiliary agent is an aqueous solution composed of benzimidazole, benzopentazole and polyethylene glycol;
Preferably, the concentration of the benzimidazole is 0.05g/L, the concentration of the benzoxazoles is 0.01g/L, and the concentration of the polyethylene glycol is 0.05g/L.
Secondly, the invention provides a preparation method of an oxalate system composite conversion film working solution for a steel matrix, wherein each 1L of the oxalate system composite conversion film working solution comprises the following steps:
(1) Weighing 0.04-2.0g of sodium citrate, adding 100mL of water, stirring until the sodium citrate is dissolved, preparing a sodium citrate aqueous solution, weighing 0.02-1.0g of cerium nitrate, adding the cerium nitrate into the sodium citrate aqueous solution, and stirring until the cerium nitrate solution is clear, thus preparing a cerium nitrate solution;
(2) Weighing 0.01-0.1g of auxiliary agent, adding 50mL of water, stirring and dissolving to prepare an auxiliary agent solution;
(3) Weighing 15-35g of oxalic acid, 0.2-2.0g of zirconium acetate, placing into a container, adding 500mL of water, and stirring until the solution is dissolved;
(4) And adding the cerium nitrate solution and the auxiliary agent solution, and adding water to 1L to obtain the oxalate system composite conversion film working solution.
Preferably, the auxiliary agent is formed by one or a combination of a plurality of benzimidazole, benzopentazole and polyethylene glycol;
In the auxiliary agent, the mass of benzimidazole is 0-0.05g, the mass of the benzopentazole is 0-0.05g, and the mass of polyethylene glycol is 0-0.10g.
Secondly, the invention provides an application method for rust prevention of a steel matrix by utilizing an oxalate system composite conversion film, which comprises the following steps:
(1) The preparation method of claim 5 is used for preparing the oxalate system composite conversion film working solution;
(2) After the steel matrix is subjected to rust removal treatment, washing the steel matrix with tap water to obtain a rust-removed steel matrix;
(3) Degreasing the derusting steel matrix, and washing with tap water to obtain a degreased steel matrix;
(4) Heating the oxalate system composite conversion film working solution in a water bath;
(5) Placing the degreased steel matrix in the heated oxalate system composite conversion film working solution for standing;
(6) Taking out the steel matrix, washing with tap water, and drying to obtain the steel matrix coated with the oxalate system composite conversion film.
Preferably, in the step (2), the degreasing treatment is performed by soaking for 5-10min with 20g/L, OP-101-4mL/L of weakly alkaline solution of sodium carbonate.
Preferably, in the step (3), the steel substrate is derusted by shot blasting, sanding or soaking in 5-10% dilute sulfuric acid at normal temperature for 5-10min.
Preferably, in the step (4), the temperature of the water bath heating is 35-65 ℃;
In the step (5), the standing time is 3-25min.
The invention has the beneficial effects that:
The invention provides a composite conversion film for a steel matrix, which is prepared by an oxalate system, wherein the electrochemical impedance of the conversion film reaches 1200-2600Ω & cm 2, the thickness of a film layer is 3-20 μm, the phase composition comprises ferric oxalate, rare earth salt and zirconium salt indissolvable matter, the microstructure is in a quadrangular prism shape, and meanwhile, the formula combinations are mutually matched to realize a synergistic antirust effect, so that the composite conversion film prepared by the invention can effectively realize the rust prevention of the steel matrix.
Drawings
FIG. 1 is a film SEM morphology of a steel substrate 2 obtained in example 1;
FIG. 2 shows the electrochemical impedance values of the films obtained by impregnating the films for different times in example 1;
FIG. 3 is an orthogonal optimization test strip;
FIG. 4 is a graph showing the electrochemical impedance value comparison of the film layers before and after addition of the auxiliary agent;
Wherein, the red curve represents no addition of auxiliary agent, and the blue curve represents addition of auxiliary agent.
Detailed Description
The following detailed description of the invention is provided in connection with the accompanying drawings that are presented to illustrate the invention and not to limit the scope thereof. The examples provided below are intended as guidelines for further modifications by one of ordinary skill in the art and are not to be construed as limiting the invention in any way.
The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are carried out according to techniques or conditions described in the literature in the field or according to the product specifications. Materials, reagents and the like used in the examples described below are commercially available unless otherwise specified.
Example 1
(1) Weighing 0.12g of sodium citrate, adding 100mL of water, stirring until the sodium citrate is dissolved to obtain a sodium citrate aqueous solution, weighing 0.06g of cerium nitrate, adding the cerium nitrate into the sodium citrate aqueous solution, and stirring until the cerium nitrate solution is clear to obtain a cerium nitrate solution;
(2) Weighing 0.05g of benzimidazole, 0.01g of benzopentazole and 0.05g of polyethylene glycol, placing in a container, adding 500mL of the mixture, and stirring the mixture until the mixture is dissolved to obtain an auxiliary agent solution;
(3) Weighing 20g of oxalic acid, placing 1.0g of zirconium acetate in a container, adding 500mL of water, and stirring until the oxalic acid and the zirconium acetate are dissolved;
(4) Adding cerium nitrate solution and auxiliary agent solution, and adding water to 1L to obtain the oxalate system composite conversion film working solution 1;
(5) Soaking a steel matrix in a weakly alkaline solution of 20g/L, OP-10-4 mL/L of sodium carbonate for 5min to perform degreasing treatment, and washing with tap water to obtain a degreased steel matrix;
(6) The method comprises the steps of polishing and derusting a degreased steel matrix by sand paper, and washing the degreased steel matrix by tap water to obtain a derusted steel matrix;
(7) Heating the oxalate system composite conversion film working solution 1 to 50 ℃ in a water bath;
(8) Placing the degreased steel matrix into the heated oxalate system composite conversion film working solution 1, and standing for 3,5,7, 10 and 15 minutes;
(9) Taking out the steel matrix, washing with tap water, and drying to obtain the steel matrix 1-5 coated with the oxalate system composite conversion film.
The thickness of the obtained film layer of the steel matrix 1-5 is about 5-15 mu m, the electrochemical impedance is 1200-2600Ω & cm, the SEM appearance of the film layer of the steel matrix 2 is shown in figure 1, and the electrochemical impedance maps of the film layers at different soaking treatment times are shown in figure 2.
Example 2
(1) Weighing 0.04g of sodium citrate, adding 100mL of water, stirring until the sodium citrate is dissolved, weighing 0.02g of cerium nitrate, adding the cerium nitrate into a sodium citrate aqueous solution, and stirring until the cerium nitrate solution is clear to obtain a cerium nitrate solution;
(2) Weighing 0.01g of benzimidazole and 0.03g of polyethylene glycol, placing in a container, adding 500mL, and stirring until the benzimidazole and the polyethylene glycol are dissolved to obtain an auxiliary agent solution;
(3) Weighing 25g of oxalic acid, placing 0.1g of zirconium acetate in a container, adding 500mL of water, and stirring until the oxalic acid and the zirconium acetate are dissolved;
(4) Adding cerium nitrate solution and auxiliary agent solution, and adding water to 1L to obtain an oxalate system composite conversion film working solution 2;
(5) Soaking a steel matrix in a weakly alkaline solution of 20g/L, OP-10-4 mL/L of sodium carbonate for 5min to perform degreasing treatment, and washing with tap water to obtain a degreased steel matrix;
(6) Activating the degreased steel matrix with 5% sulfuric acid to remove rust for 10min, and washing with tap water to obtain a rust-removed steel matrix;
(7) Heating the oxalate system composite conversion film working solution 2 to 55 ℃ in a water bath;
(8) Placing the degreased steel matrix into the heated oxalate system composite conversion film working solution 2, and standing for 15min;
(9) Taking out the steel matrix, washing with tap water, and drying to obtain the steel matrix 6 coated with the oxalate system composite conversion film.
The thickness of the film of the steel matrix 6 obtained is about 15 μm, and the electrochemical impedance reaches 2000 Ω cm 2.
Example 3
(1) Weighing 2.00g of sodium citrate, adding 100mL of water, stirring until the sodium citrate is dissolved, weighing 1.00g of cerium nitrate, adding the cerium nitrate into a sodium citrate aqueous solution, and stirring until the cerium nitrate solution is clear to obtain a cerium nitrate solution;
(2) Weighing 0.05g of benzimidazole, 0.05g of benzopentazole and 0.01g of polyethylene glycol, placing in a container, adding 500mL of the mixture, and stirring the mixture until the mixture is dissolved to obtain an auxiliary agent solution;
(3) Weighing 30g of oxalic acid, placing 1g of zirconium acetate in a container, adding 500mL of water, and stirring until the oxalic acid and the zirconium acetate are dissolved;
(4) Adding cerium nitrate solution and auxiliary agent solution, and adding water to 1L to obtain an oxalate system composite conversion film working solution 3;
(5) Soaking a rust steel matrix in a weak alkaline solution of 20g/L, OP-10-4 mL/L of sodium carbonate for 5min for degreasing treatment, and washing with tap water to obtain a degreased steel matrix;
(6) Activating the steel matrix with 5% sulfuric acid to remove rust for 10min, and washing with tap water to obtain a rust-removed steel matrix;
(7) Heating the oxalate system composite conversion film working solution 3 to 55 ℃ in a water bath;
(8) Placing the degreased steel matrix into the heated oxalate system composite conversion film working solution 3, and standing for 5min;
(9) Taking out the steel matrix, washing with tap water, and drying to obtain the steel matrix 7 coated with the oxalate system composite conversion film.
The thickness of the film of the steel matrix 7 obtained is about 8 μm, and the electrochemical impedance reaches 1500 Ω cm 2.
Example 4
The embodiment detects the influence of different cerium salt dosage on the corrosion resistance of the film
The addition amount of cerium nitrate and the obtained results are shown in Table 1, and the addition amount of the other components except sodium citrate in the formulation was changed depending on cerium nitrate, and the standing treatment time was 15 minutes as in example 1.
Table 1 effect of concentration of cerium nitrate (cerium nitrate: sodium citrate=1:2) on results of copper sulfate drip experiments of conversion film
As can be seen from Table 1, the corrosion resistance of the film layer is remarkably improved after cerium nitrate is added, the film layer corrosion resistance overall shows a trend of increasing along with the increase of the concentration in the solution after the concentration is 0.02g/L, but when the concentration is too large, the film layer is difficult to thicken, so that the addition amount of the cerium nitrate is controlled to be 0.02-1.0g/L.
Example 5
The embodiment detects the influence of different zirconium salt dosage on the corrosion resistance of the film
The addition amount of zirconium acetate and the obtained results are shown in Table 2, and the rest of the components in the formulation were the same as in example 1, and the standing treatment time was 15 minutes.
TABLE 2 influence of different zirconium acetate concentrations on the results of the copper sulfate drop experiments on the conversion film
As can be seen from Table 2, the addition of zirconium acetate in an appropriate amount can improve the corrosion resistance of the film, but when the addition amount of zirconium acetate exceeds 2.0g, the corrosion resistance of the film is lowered, so that the addition amount of zirconium acetate in the present invention is controlled to be 0.2-2.0g/L.
Example 6
The three-factor three-level orthogonal optimization test of the auxiliary agent is carried out, the factor level is shown in table 3, the obtained experimental data are shown in table 4, and specific samples are shown in fig. 3.
TABLE 3 factor level Table
TABLE 4 results of orthogonal optimization experiments
It can be seen from table 4 that the three adjuvants have a better synergistic effect, with the effect of the benzopentazole being greatest, followed by the polyethylene glycol, and again by the benzimidazole.
Example 7
This example detects the effect of the addition of an auxiliary agent on the corrosion resistance of the film
The amount of the additive was the same as in example 1, and the heating temperature was 50℃to obtain the results shown in FIG. 4.
As can be seen from fig. 4, the addition of the auxiliary agent greatly improves the resistance value of the film layer, which indicates that the addition of the auxiliary agent has a significant effect on the corrosion resistance of the film layer.

Claims (10)

1.一种用于钢铁基体的草酸盐体系复合转化膜,其特征在于,所述草酸盐体系复合转化膜的制备原料由如下组分组成:草酸、柠檬酸钠、硝酸铈、醋酸锆和助剂。1. An oxalate system composite conversion coating for a steel substrate, characterized in that the raw materials for preparing the oxalate system composite conversion coating consist of the following components: oxalic acid, sodium citrate, cerium nitrate, zirconium acetate and additives. 2.根据权利要求1所述的一种用于钢铁基体的草酸盐体系复合转化膜,其特征在于,所述草酸盐体系复合转化膜的制备原料中,所述草酸的浓度为15-35g/L,所述柠檬酸钠的浓度为0.04-2.0g/L,所述硝酸铈的浓度为0.02-1.0g/L,所述醋酸锆的浓度为0.2-2.0g/L,所述助剂的浓度为0.01-0.1mg/L。2. The oxalate system composite conversion coating for a steel substrate according to claim 1, characterized in that, in the raw materials for preparing the oxalate system composite conversion coating, the concentration of oxalic acid is 15-35 g/L, the concentration of sodium citrate is 0.04-2.0 g/L, the concentration of cerium nitrate is 0.02-1.0 g/L, the concentration of zirconium acetate is 0.2-2.0 g/L, and the concentration of the additive is 0.01-0.1 mg/L. 3.根据权利要求2所述的一种用于钢铁基体的草酸盐体系复合转化膜,其特征在于,所述助剂为由苯并咪唑、苯并五氮唑、聚乙二醇中的一种或者几种组合形成的水溶液。3. An oxalate system composite conversion coating for a steel substrate according to claim 2, characterized in that the additive is an aqueous solution formed by one or a combination of benzimidazole, benzopentazole, and polyethylene glycol. 4.根据权利要求3所述的一种用于钢铁基体的草酸盐体系复合转化膜,其特征在于,所述助剂中,所述苯并咪唑的浓度为0-0.05g/L,所述苯并五氮唑的浓度为0-0.05g/L,所述聚乙二醇的浓度为0-0.10g/L。4. The oxalate system composite conversion coating for a steel substrate according to claim 3, characterized in that, in the additive, the concentration of the benzimidazole is 0-0.05 g/L, the concentration of the benzopentazole is 0-0.05 g/L, and the concentration of the polyethylene glycol is 0-0.10 g/L. 5.一种用于钢铁基体的草酸盐体系复合转化膜工作液的制备方法,其特征在于,每1L所述草酸盐体系复合转化膜工作液的制备方法包括如下步骤:5. A method for preparing an oxalate system composite conversion coating working solution for a steel substrate, characterized in that the method for preparing the oxalate system composite conversion coating working solution comprises the following steps per 1L of the oxalate system composite conversion coating working solution: (1)称取0.04-2.0g柠檬酸钠,加水100mL,搅拌至溶解,制备得到柠檬酸钠水溶液,再称取0.02-1.0g硝酸铈,加至所述柠檬酸钠水溶液中,搅拌至澄清,制备得到硝酸铈溶液;(1) weighing 0.04-2.0 g of sodium citrate, adding 100 mL of water, stirring until dissolved, to prepare a sodium citrate aqueous solution, then weighing 0.02-1.0 g of cerium nitrate, adding it to the sodium citrate aqueous solution, stirring until clear, to prepare a cerium nitrate solution; (2)称取0.01-0.1g助剂,加水50mL,搅拌溶解,制备得到助剂溶液;(2) Weigh 0.01-0.1 g of an auxiliary agent, add 50 mL of water, stir and dissolve to prepare an auxiliary agent solution; (3)称取15-35g草酸,0.2-2.0g醋酸锆,置于容器中,加水500mL,搅拌至溶解;(3) Weigh 15-35 g oxalic acid and 0.2-2.0 g zirconium acetate, place in a container, add 500 mL of water, and stir until dissolved; (4)加入所述硝酸铈溶液与所述助剂溶液,加水至1L,即得到所述草酸盐体系复合转化膜工作液。(4) Add the cerium nitrate solution and the auxiliary agent solution, and add water to 1 L to obtain the oxalate system composite conversion membrane working solution. 6.根据权利要求5所述的一种用于钢铁基体的草酸盐体系复合转化膜工作液的制备方法,其特征在于,所述助剂由苯并咪唑、苯并五氮唑、聚乙二醇中的一种或者几种组合形成;6. The method for preparing an oxalate system composite conversion coating working fluid for a steel substrate according to claim 5, characterized in that the auxiliary agent is formed by one or a combination of benzimidazole, benzopentazole, and polyethylene glycol; 所述助剂中,苯并咪唑的质量为0-0.05g,所述苯并五氮唑的质量为0-0.05g,所述聚乙二醇的质量为0-0.10g。In the auxiliary agent, the mass of benzimidazole is 0-0.05g, the mass of benzopentazole is 0-0.05g, and the mass of polyethylene glycol is 0-0.10g. 7.一种利用草酸盐体系复合转化膜进行钢铁基体防锈的应用方法,其特征在于,所述应用方法包括如下步骤:7. An application method for rust prevention of steel substrates using an oxalate system composite conversion film, characterized in that the application method comprises the following steps: (1)按照权利要求5所述的制备方法制备得到草酸盐体系复合转化膜工作液;(1) preparing an oxalate system composite conversion membrane working solution according to the preparation method of claim 5; (2)将钢铁基体进行脱脂处理后,经水水洗,得到脱脂钢铁基体;(2) degreasing the steel substrate and then washing it with water to obtain a degreased steel substrate; (3)将所述脱脂钢铁基体进行除锈处理后,经水水洗,得到除锈钢铁基体;(3) subjecting the degreased steel substrate to rust removal treatment, and then washing with water to obtain a rust-removed steel substrate; (4)将所述草酸盐体系复合转化膜工作液进行水浴加热;(4) heating the oxalate system composite conversion membrane working solution in a water bath; (5)将所述脱脂除锈钢铁基体置于加热后的所述草酸盐体系复合转化膜工作液中静置;(5) placing the degreased and rust-removed steel substrate in the heated oxalate system composite conversion coating working solution and allowing it to stand; (6)取出钢铁基体,经水水洗后,干燥得到包覆草酸盐体系复合转化膜的钢铁基体。(6) The steel substrate is taken out, washed with water, and then dried to obtain a steel substrate coated with an oxalate system composite conversion film. 8.根据权利要求7所述的一种利用草酸盐体系复合转化膜进行钢铁基体防锈的应用方法,其特征在于,所述步骤(2)中,所述脱脂处理的方式为采用碳酸钠20g/L、OP-10 1-4mL/L的弱碱性溶液浸渍5-10min。8. The method for applying oxalate system composite conversion film to rust prevention of steel substrate according to claim 7, characterized in that in the step (2), the degreasing treatment is carried out by immersing in a weak alkaline solution of 20 g/L sodium carbonate and 1-4 mL/L OP-10 for 5-10 min. 9.根据权利要求8所述的一种利用草酸盐体系复合转化膜进行钢铁基体防锈的应用方法,其特在于,所述步骤(3)中,所述钢铁基体除锈的方式为抛丸,砂纸打磨,或5-10%稀硫酸常温下浸渍5-10min。9. The method for rust prevention of steel substrates using an oxalate system composite conversion film according to claim 8, wherein in step (3), the steel substrate is rust-removed by shot blasting, sandpaper polishing, or immersion in 5-10% dilute sulfuric acid at room temperature for 5-10 minutes. 10.根据权利要求9所述的一种利用草酸盐体系复合转化膜进行钢铁基体防锈的应用方法,其特在于,所述步骤(4)中,所述水浴加热的温度为35-65℃;10. The method for applying the oxalate system composite conversion film to rust-proof steel substrate according to claim 9, wherein in the step (4), the water bath heating temperature is 35-65°C; 所述步骤(5)中,所述静置的时间为3-25min。In the step (5), the standing time is 3-25 min.
CN202410304222.6A 2024-03-18 2024-03-18 An oxalate system composite conversion film for steel substrate and its application method Pending CN118166345A (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN202410304222.6A CN118166345A (en) 2024-03-18 2024-03-18 An oxalate system composite conversion film for steel substrate and its application method

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN202410304222.6A CN118166345A (en) 2024-03-18 2024-03-18 An oxalate system composite conversion film for steel substrate and its application method

Publications (1)

Publication Number Publication Date
CN118166345A true CN118166345A (en) 2024-06-11

Family

ID=91346599

Family Applications (1)

Application Number Title Priority Date Filing Date
CN202410304222.6A Pending CN118166345A (en) 2024-03-18 2024-03-18 An oxalate system composite conversion film for steel substrate and its application method

Country Status (1)

Country Link
CN (1) CN118166345A (en)

Citations (4)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
GB1072724A (en) * 1965-04-26 1967-06-21 Pyrene Co Ltd Improvements in the coating of metal surfaces
EP0233503A1 (en) * 1986-01-27 1987-08-26 Nihon Parkerizing Co., Ltd. Process for applying oxalate coatings to stainless steel
JP2008169405A (en) * 2007-01-09 2008-07-24 Daido Steel Co Ltd Manufacturing method of stainless steel wire with excellent cold forgeability
CN109207972A (en) * 2018-11-26 2019-01-15 武汉材料保护研究所有限公司 A kind of preparation method of aluminum alloy surface titanium zirconium cerium chemical composition coating

Patent Citations (4)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
GB1072724A (en) * 1965-04-26 1967-06-21 Pyrene Co Ltd Improvements in the coating of metal surfaces
EP0233503A1 (en) * 1986-01-27 1987-08-26 Nihon Parkerizing Co., Ltd. Process for applying oxalate coatings to stainless steel
JP2008169405A (en) * 2007-01-09 2008-07-24 Daido Steel Co Ltd Manufacturing method of stainless steel wire with excellent cold forgeability
CN109207972A (en) * 2018-11-26 2019-01-15 武汉材料保护研究所有限公司 A kind of preparation method of aluminum alloy surface titanium zirconium cerium chemical composition coating

Non-Patent Citations (4)

* Cited by examiner, † Cited by third party
Title
HENG ZHANG ET AL.: ""The structure, corrosion resistance, and formation mechanism of a composite conversion film based on oxalate on steel substrates"", 《SURFACES AND INTERFACES》, 19 February 2025 (2025-02-19), pages 1 - 14 *
YONG LU ET AL.: ""Effect of Rare-earth Salts on Corrosion Resistance of Phytic Acid Based Conversion Coatings on Q235 Steel"", 《INTERNATIONAL JOURNAL OF ELECTROCHEMICAL SCIENCE》, 28 June 2023 (2023-06-28), pages 7968 - 7981 *
崔永辉等: ""添加剂对铝合金稀土转化膜的影响"", 《表面技术》, 20 May 2019 (2019-05-20), pages 225 - 231 *
董首山: "化学转化膜――第四讲 草酸盐处理", 腐蚀科学与防护技术, no. 02, 30 June 1990 (1990-06-30) *

Similar Documents

Publication Publication Date Title
CN106810993B (en) Self-healing type epoxy coating and its preparation and application based on the mesoporous container of micron order
CN102899653B (en) Stainless steel passivation water solution and preparation method thereof
CN107190254A (en) A kind of new brown treatment fluid of printed circuit board
CN116590698B (en) Treating agent for forming chemical film layer on metal surface and preparation method thereof
CN116694183B (en) Magnesium alloy double-layer organic composite coating and preparation method thereof
CN115354128A (en) Pickling process of corrosion-resistant stainless steel band
CN102965655A (en) Method for improving corrosion resistance of phosphate coating on surface of neodymium-iron-boron permanent magnet
CN111235576A (en) Method for constructing micro-nano porous organic acid pretreatment layer on metal surface and application
CN115216759A (en) A kind of hydrophilic chemical conversion film-forming liquid and aluminum alloy surface treatment method
CN105506605A (en) Weather-resistant steel rust layer stabilizing treatment fluid
KR102769763B1 (en) Acid zinc sulfate metal pretreatment
CN115537790A (en) A phosphating solution and phosphating method for preparing a highly alkali-resistant phosphating film on the surface of a galvanized sheet
CN113789507A (en) Zinc-calcium-manganese phosphating solution and preparation method thereof
CN114836741A (en) Steel substrate surface film forming solution based on organic-inorganic chelating compounding and preparation and application thereof
CN111690933B (en) Deplating solution and deplating method for unqualified cadmium-plated layer
CN116875170B (en) Chromium-free zinc-aluminum coating material for high-strength fasteners and coating method thereof
CN114737189B (en) Method for preparing surface pretreatment layer
WO2024087548A1 (en) Surface treatment method for permanent magnet, permanent magnet and protective film thereof
CN111349920A (en) A kind of environment-friendly phosphating liquid containing rare earth composite accelerator and using method
CN115142055B (en) Hydrophobic chemical conversion film forming liquid and aluminum alloy surface treatment method
CN114318466A (en) A kind of preparation method of anti-corrosion aluminum profile
CN115216757A (en) Copper plating solution and copper plating method for carbon steel maintenance tools in petrochemical industry
CN114686864A (en) Environment-friendly organic passivation corrosion prevention technology suitable for surface of steel material
CN114892155A (en) Normal-temperature blackening treatment liquid for alloy steel surface and method for blackening alloy steel surface at normal temperature
CN108220938B (en) Ultra-thin film type room temperature low-slag phosphating solution and synthesis method thereof

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination